Penggunaan Media Power Point untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS Siswa Kelas V SDN 118275 Sialang Pamoran II Kecamatan Silangkitang - Susmiati Susmiati (PGSD UMN Al-Washliyah, 2021)
This study was based on the low student learning outcomes in the social studies subject. It is known that students have daily test scores that do not reach the predetermined KKM score. The purpose of this study was to improve student learning outcomes during the social studies learning process by applying the use of power point media. This study used a classroom action research method that used a qualitative descriptive research approach. Conducted in two cycles and each cycle consisting of planning, implementing and observing, reflecting. The subjects of this study were students of grade V SDN 118275 Sialang Pamoran II, totaling 28 students with 13 male students and 15 female students. Data collection techniques using the method of observation and learning outcomes tests. The results showed that during the learning process there was an increase with the percentage of completeness of 64% in cycle I and 86% in cycle II. The type of research used was Classroom Action Research (PTK), which was conducted in two cycles. Each cycle is carried out for 2 meetings. Data collection techniques in this study used observation, test and student response techniques. The collected data were analyzed using descriptive qualitative and quantitative techniques. The results showed that the percentage of the implementation of learning in teacher activities in cycle I obtained 69% and cycle II gained 88%. In student activities also increased from 75% in cycle I and 93% in cycle II. Thus it can be concluded that the application of learning using power point media can improve social studies learning outcomes of class VI SDN 118275 Sialang Pamoran II Silangkitang.